Deep breathing exercise at work: Potential applications and impact - Tavoian, Dallin; Craighead, Daniel H. (Frontiers in Physiology, 2023)
Hypertension is a major contributor to cardiovascular disease and daily deep breathing exercise (DBE) is a promising intervention to reduce blood pressure and stress in adults. DBE is simple, time-efficient, and does not require specialized equipment, allowing participation in a wide variety of settings. The workplace is an ideal setting to implement DBE at the national level for several reasons, including a large proportion of waking hours spent in the workplace, high levels of sedentary time at work, prevalence of work-related stress, and regular breaks throughout the day potentially reducing worker error. While the degree of adherence to daily workplace DBE will be the responsibility of the individual, employers and managers can (and should) do much to remove barriers to participation. Specifically, this could include: implementing regular short breaks or classes to perform DBE throughout the day, covering subscription costs for smartphone applications that guide DBE, and creating incentive programs for continuing DBE participation. Implementing DBE in the workplace is a pragmatic approach to provide a low-cost blood pressure and stress reduction therapy to a substantial portion of the adult population in the US, at least 50% of whom have high blood pressure.